KETELADANAN MANAGEMEN EMOSI PEMIMPIN YANG BERDAMPAK POSITIF BAGI KOMUNITAS REMAJA KRISTEN - Martinus, Marlina; Santosa, Monica (STT KINGDOM BALI, 2026)
This article explains how the exemplary emotional management of a leader in a Christian youth community, and the causes of the leader's anger. Management is the management of everything, and emotions are feelings that cause various feelings and thoughts. So it is very important for leaders to manage excessive emotional problems. In this article, the author writes several problems that can help leaders become integrity. In this article's research, the author uses qualitative methods, literature studies, with studies from books, journals that can help the author find data and describe the contents of the discussion. The results of this study explain the importance of emotional management in leadership, which brings an example to the community and others. Therefore, emotional management that has a positive impact on the Christian youth community can be emulated positively by Christian youth.